Modal Sosial Pedagang Sayur di ‘’Pasar Tradisional Berbasis Modern’’ Teluk Kuantan Kabupaten Kuantan Singingi - Annisa Dwi Elsa Refina; Yusmar Yusuf (Peneliti.net, 2026)
The role of social capital in trading is also very important for the sustainability of traders in the market. With social capital in the form of networks, trust and norms practised by traders in the market, it will strengthen the sustainability of the traders' businesses. The objectives of this study are: 1) to examine how social capital is practised among vegetable traders, suppliers and buyers; 2) to identify the most dominant social capital established between traders and buyers or suppliers in market activities. To achieve these objectives, a descriptive qualitative research method was used with five informants. This study used purposive sampling, which was carried out by selecting samples and through a process of selecting subjects or units of analysis that would be the focus of the study based on certain criteria relevant to the research objectives. The results of this study show that there are elements of social capital carried out by vegetable traders. With the existence of social networks, trust and norms, it will be easier to run a business, especially for these traders. Judging from their interactions, they always prioritise the element of networks because if this element is in place, it will attract the elements of trust and norms. The results regarding market security and cleanliness have been very good, thanks to the efforts of the officers, especially since they pay security fees every day.